High rise building movement monitoring using RTK-GPS (case study: Menara Sarawak Enterprise) - Shu, Kian Kok (2005)
The need for deformation surveys of large engineering structures such as long span bridges, dams and tall structures often arises from concerns associated with environmental protection, property damage and public safety. There are many high buildings nowadays, therefore it is very important to monitor the buildings to ensure they are still under stable condition. Recently, the Global Positioning System (GPS) especially Real Time Kinematics (RTK-GPS) has emerged as a survey tool for many deformation applications. The RTK-GPS is carrier phase observation processed in real time, giving results such as position coordinates. This study highlights the concept and methodology of the continuous RTK-GPS and its potential application for high rise building monitoring surveys. The main objectives of this study are to study the ability and efficiency of the continuous RTK-GPS method in high rise building’ deformation detection and also to develop KFilter program for movement monitoring using Matlab v6.1 with Kalman Filter method. The GPS instruments’ calibrations had been carried out to ensure accuracy and reliability of the continuous RTK-GPS observation for high rise building movement monitoring. The surveys had been carried out on Menara Sarawak Enterprise, Johore Malaysia in two different epochs. Thus, the developed KFilter program is able to perform the movement monitoring analysis on the observed data to classify the stability of the building. The results of this study shows that the continuous RTK-GPS can provide 1cm and 2cm accuracy for horizontal and vertical respectively. The effectiveness of this technique depends on radio link communication whereby obstructions will cause the communication signal to fail. From the KFilter program analysis, the results shows that the Menara Sarawak Enterprise building is stable. The continuous RTK-GPS epoch 1 and epoch 2 analyses had shown the building is stable although displacement distance around 0.5cm and 1cm respectively are detected.